(untitled) (Research, Society and Development, 2019)
This article aims to contribute to the theoretical reflections on the State and the dimensions of politics, highlighting its territorial dimension. This is a bibliographic research that sought to synthetically expose the different theoretical currents about State, from Political Geography to Political Science.